Long‐term on‐farm participatory maize breeding by stratified mass selection retains molecular diversity while improving agronomic performance. (14th October 2017) - Alves, Mara Lisa; Belo, Maria; Carbas, Bruna; Brites, Cláudia; Paulo, Manuel; Mendes‐Moreira, Pedro; Brites, Carla; Bronze, Maria do Rosário; Šatović, Zlatko; Vaz Patto, Maria Carlota
Abstract: Modern maize breeding programs gave rise to genetically uniform varieties that can affect maize's capacity to cope with increasing climate unpredictability. Maize populations, genetically more heterogeneous, can evolve and better adapt to a broader range of edaphic–climatic conditions. These populations usually suffer from low yields; it is therefore desirable to improve their agronomic performance while maintaining their valuable diversity levels. With this objective, a long‐term participatory breeding/on‐farm conservation program was established in Portugal. In this program, maize populations were subject to stratified mass selection. This work aimed to estimate the effect of on‐farm stratified mass selection on the agronomic performance, quality, and molecular diversity of two historical maize populations. Multilocation field trials, comparing the initial populations with the derived selection cycles, showed that this selection methodology led to agronomic improvement for one of the populations. The molecular diversity analysis, using microsatellites, revealed that overall genetic diversity in both populations was maintained throughout selection. The comparison of quality parameters between the initial populations and the derived selection cycles was made using kernel from a common‐garden experiment. This analysis showed that the majority of the quality traits evaluated progressed erratically over time. In conclusion, this breeding approach, through simple and low‐cost methodologies, proved to be an alternative strategy for genetic resources' on‐farm conservation.